2017
DOI: 10.1051/ctv/20173201042
|View full text |Cite
|
Sign up to set email alerts
|

Effects of surface and subsurface drip irrigation on physiology and yield of ‘Godello’ grapevines grown in Galicia, NW Spain

Abstract: SUMMARYIrrigation has been considered a controversial practice in European traditional viticulture due to potential alterations in the balance between vegetative growth and yield. In this regard, the influence of surface (DI) and subsurface (SDI) drip irrigation on physiological performance of the 'Godello' grapevine (Vitis vinifera L.) cultivar was compared with a non-irrigated control (R) over three consecutive growing seasons (2012)(2013)(2014) in NW Spain. Irrigation improved vine water status; R plants re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…Previous studies reported data on the effects of irrigation on physiology and yield response of vines in this site [7,19]. In summary, rain-fed vines showed more negative midday stem water potentials than those irrigated; whereas yield and cluster weight were similar among treatments (Table 2).…”
Section: Resultsmentioning
confidence: 73%
See 4 more Smart Citations
“…Previous studies reported data on the effects of irrigation on physiology and yield response of vines in this site [7,19]. In summary, rain-fed vines showed more negative midday stem water potentials than those irrigated; whereas yield and cluster weight were similar among treatments (Table 2).…”
Section: Resultsmentioning
confidence: 73%
“…These findings contrasted with the results from the current study likely because of the different cultivar/rootstock combination and climate conditions. In fact, soil water availability was adequate for bud-break and the development of leaf surface in our study [7,19], so no differences in grapevine metabolism were expected.…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations